Does Good School Governance (GSG) Improve on The Management Performance of School Operational Assistance (BOS) - Sohidin, Sohidin; Rahmawati, Rahmawati; Djuminah, Djuminah; Gantyowati, Evi (Universitas Negeri Semarang, 2023)
The management of BOS funds in education units requires governance that can ensure that these funds can be used appropriately in teaching and learning activities. BOS funds are also intended to ensure the continuous education of students from the primary education level to the secondary education level so that they are expected to bring benefits to the community equally. The purpose of the study was to provide empirical evidence of the influence of GSG on the performance of BOS fund management when compared with the calculation of value for money. The research sample is the State Vocational High School (SMK) at the Central Java province level, totaling 238 in the 2019-2021 period. The sampling technique in this study used probability sampling with SEM analysis tools. The conclusion of this study is that GSG has a positive effect on the performance of BOS fund management. However, the results of the calculation of value for money in the management and utilization of BOS funds are less economical and less efficient. So that the improved performance is not accompanied by economical and efficient management.